2013
DOI: 10.1136/jnnp-2013-304951
|View full text |Cite
|
Sign up to set email alerts
|

Characterising aggressive multiple sclerosis

Abstract: Objective To explore the occurrence and characteristics of aggressive multiple sclerosis (AMS) in adult-onset multiple sclerosis (MS) patients. Methods Prospectively collected data from British Columbia, Canada, were retrospectively analysed. AMS was defined in three different ways (AMS1, 2 and 3): 'AMS1'-confirmed Expanded Disability Status Scale (EDSS) ≥6 within 5 years of MS onset; 'AMS2'-confirmed EDSS ≥6 by age 40; and 'AMS3'-secondary progressive MS within 3 years of a relapsing-onset course. Three resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 36 publications
1
70
1
5
Order By: Relevance
“…The term fulminant MS, although adopted previously, is currently associated with Marburg' s variant in which progression is monophasic with inexorable deterioration and rapid death 7 . Malignant/aggressive forms occur in 4-14% of cases 3,4 ; and this Brazilian cohort, in which 8.5% of patients developed severe disability within five years, confirmed these data. This percentage includes both RRMS and PPMS; however, if only the former were considered, this rate would fall to 5.8%.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The term fulminant MS, although adopted previously, is currently associated with Marburg' s variant in which progression is monophasic with inexorable deterioration and rapid death 7 . Malignant/aggressive forms occur in 4-14% of cases 3,4 ; and this Brazilian cohort, in which 8.5% of patients developed severe disability within five years, confirmed these data. This percentage includes both RRMS and PPMS; however, if only the former were considered, this rate would fall to 5.8%.…”
Section: Discussionsupporting
confidence: 78%
“…Certain patients reach greater degrees of disability within a short period of time. This severe progressive form is referred to as malignant multiple sclerosis (MMS) when an Expanded Disability Status Scale (EDSS) score of 6 is reached within five years of disease onset 3,4 . Early recognition of potentially severe cases based on prognostic factors is crucial when making therapeutic decisions to reduce the risk of disability and impaired quality of life.…”
Section: Articlementioning
confidence: 99%
“…We found that the risk of death was increased in the year after ICU admission. The particularly high mortality rate among young persons raised the question of whether this was attributable to aggressive MS, 29 infection, or other causes. Although limited by small numbers, our findings did not suggest that aggressive MS had a differentially greater role at young ages.…”
Section: Resultsmentioning
confidence: 99%
“…11,21 Many terms have been proposed for this phenomenon-malignant MS, aggressive MS, catastrophic MS, fulminant MS-with a seemingly equal number of definitions, both qualitative and quantitative. [22][23][24] The lack of consensus likely stems from the difficulty of applying a uniform definition of severe MS to patients in different stages of the disease, as can be illustrated with the following examples.…”
Section: Herbert's Definition Of Aggressive Msmentioning
confidence: 99%